Barriers and Facilitators of Reflective Practice in Counsellor (Canadian Journal of Counselling and Psychotherapy, 2008)
This qualitative study involved five doctoral counselling students from a major Canadian university who shared critical incidents of barriers and facilitators of reflective practice in their graduate experiences. Sixteen incidents engendered reflection while eight hindered open reflection. Conditions found to facilitate reflective practice included (a) experiencing a trusting relationship, (b) opening up with fellow students, (c) engaging in reflective tasks, (d) having self-trust/risking, and (e) interacting with supportive academic personnel. Conditions found to create barriers to open reflection included (a) experiencing mistrust/ unsafe relationship, (b) interacting with non-reflective fellow students, (c) receiving unsupportive/jarring feedback, (d) facing a systemic barrier/unsafe educational landscape, and (e) interacting with unsupportive academic personnel. Research limitations as well as implications and recommendations for counsellor development and directions for future research are provided.